2007
DOI: 10.1136/pgmj.2007.057570
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous administration of metoclopramide by 2 min bolus vs 15 min infusion: does it affect the improvement of headache while reducing the side effects?

Abstract: Objective: To determine the therapeutic effect (alleviation of vascular type headache) and side effects of a slow intravenous metoclopramide infusion over 15 min compared with those effects of a bolus intravenous metoclopramide infusion over 2 min in the treatment of patients with recent onset vascular type headache. Material and methods: All adults treated with metoclopramide for vascular type headache were eligible for entry into this clinical randomised double blinded trial. This study compared the effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 35 publications
2
16
0
1
Order By: Relevance
“…In both groups we observed that on average, in the fifth minute, the nausea scores decreased to half. The results of this study are similar in some aspects to previous ones 2 9 10 12 19 20…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In both groups we observed that on average, in the fifth minute, the nausea scores decreased to half. The results of this study are similar in some aspects to previous ones 2 9 10 12 19 20…”
Section: Discussionsupporting
confidence: 90%
“…In the studies in which bolus infusion administrations of metoclopramide were compared, which were sufficient in terms of sampling, and were prospective, randomised, double blind trials, it was observed that slow infusion significantly reduced the percentage of akathisia 2 3 9 10 12 20 21. Akathisia can go unnoticed by physicians, especially in busy EDs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, metoclopramide given as an infusion over 15 min is less likely to cause akathisia than if the same dose is given as a bolus over 2 min (5.8% vs. 24.7%, respectively; p Ͻ 0.001) (43). This observation is replicated in another study in patients with headache that reported a 78% relative risk reduction of akathisia with an infusion over 15 min (44). There was no loss of efficacy with regard to symptom relief by slower administration in these investigations.…”
Section: Prochlorperazine and Metoclopramidementioning
confidence: 61%